(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2010)
This prospective study was done in Combined Military Hospital, Dhaka from July 2002 to June 2003 to document the postnatal changes of thyroid hormones in full term low birth weight (LBW) neonates. The parameters were- serum TT4 (total thyroxin), TT3 (total triiodothyronine), FT4 (free thyroxin) and TSH (thyroid stimulating hormone). Twenty seven healthy full term neonates formed the control group (group A) who were studied on day 5 to observe the base line data. Study group (group B) consisted of 27 low birth weight (LBW) neonates. They were studied twice on day 5 (B1) and day 45 (B2). The mean ± SD gestational age was 38.41±0.93 and 38.63±1.08 weeks in group A and B respectively. The mean ± SD birth weight were 3.41±0.55 and 2.11±0.33 kg in group A and B respectively and the difference was statistically significant (p <0.0001). All neonates of group A had normal serum levels of TT4, TT3, FT4 and TSH on day 5 but in LBW full term neonates though FT4 level remained within normal range, 48% neonates of group B had significantly decreased levels of TT4, TT3 and TSH (p<0.001) but on day 45 all of these hormone levels were significantly increased (p<0.001) and attained normal values. This study showed that 48% LBW neonates had transient hypothyroxinaemia on day 5 which was corrected spontaneously by day 45. Key words: Hypothyroxinaemia; Low birth weight (LBW). DOI: 10.3329/jafmc.v6i1.5984 Journal of Armed Forces Medical College, Bangladesh Vol.6(1) 2010 p.8-11